Economic Approach in Structuring the Creative Industries - Borisova, Vladia (UNWE Yearbook, 2017)
The study explores a new approach to structuring the creative industries by introducing the issue by bringing the intellectual property as a classification criterion of the creative industries’ system. Three main types of creative industries have been identified: creative industries in the sector of education and science; innovation industries in the sector of material production and cultural industries in the sector of culture. A comparative analysis between creative industries and the industries in the traditional production has been made. The specifics of the clusters and the local production systems in the creative sector have been examined and their characteristics have been identified as structural formations therein. The study outlines and analyses the main structural units in the creative industries functionally linked via the creation and use of intellectual property objects for business purposes. The focus of the study is the structure of business networks in the creative industries. In the creative industries business primarily involves operations with intellectual property. That is why, in order to position the structural units along the value chain of the creative industries, the following are extracted and analyzed: educational and scientific infrastructure and innovation infrastructure of the country. The study goes deeply into the two core business models applicable to creative industries: academy to business and business to business.